Strategic Mismatches in Competing Teams - Matthias Kräkel (Institute for the Study of Labor (IZA), 1999)
This paper discusses the strategic role of mismatching, where players voluntarily form inefficient teams or forego the formation of efficient teams, respectively. Strategic mismatching can be rational when players realize a competitive advantage (e.g. harming other competitors). In addition, the results show that free riding can be beneficial for a team in combination with strategic mismatching and that the loser?s curse may be welfare improving by mitigating the problem of strategic mismatching.
Keywords: J44; J41; D21; C72; 330; Economies of scope; free-rider effect; mismatch; teams; tournament; Wettbewerb; Markteintritt; Vertragstheorie; Nichtkooperatives Spiel; Trittbrettfahrerverhalten; Asymmetrische Information; Theorie; Tournament